A nearly zero temperature gradient furnace system for high pressure multi-anvil experiments. Issue 3 (3rd July 2018) - Zarei, Alireza; Li, Yang; Fei, Hongzhan; Katsura, Tomoo
ABSTRACT: A new furnace system with an almost zero temperature gradient throughout the sample area was designed for multi-anvil high pressure experiments. Test experiments of the new design were performed using 18/11 and 25/15 cell assemblies at 4 GPa, 1400°C and 1500°C, respectively. The temperature field within the sample capsules appeared to be very homogenous as indicated by Mg2 Si2 O6 –MgCaSi2 O6 two-pyroxene thermometry, by direct temperature measurements using two thermocouples within the same assembly, and by distribution of solid and liquid phases in the sample capsule. The temperature gradient is estimated to be <2.4°C/mm over an area of 4 × 5 mm 2 within the furnace. It is significantly lower than standard multi-anvil experiments with straight or stepped furnace systems, which are at the levels of 20–200°C/mm.